Waste paper sludge ash and ground granulated blast furnace slag as binder in concrete - Gailius, Albinas; Laurikietytė, Živilė (Journal of Civil Engineering and Management, 2003)
The aim of the research was to develop an economic binder from waste products that could have applications in the production of concrete. Portland cement (PC) production is a very high-energy intensive process that also involves significant environmental damage with respect to CO2 production and raw material acquisition. This paper investigates workability and strength of concrete made with different proportions of waste paper sludge ash (WSA) and ground granulated blast-furnace slag (GGBS) as binder, at two w/b rations: 0,5 and 0,4. Specimens were tested unconfined compressive strength after 1, 7, 28 and 90 days of curing. The results obtained show that 28 days strength varies between 15–21 MPa, and the general trend of strength development with increasing WSA content has the shape of an inverse parabola, where the highest 28 days and 90 day strengths are achieve by concrete with a mix composition of 50:50 at both w/b ratios. Workability was evaluated by a slump test. Superplasticiser Daracem SP 1 was used for the concrete with WSA – GGBS binder in order to obtain workability, comparable to the observed for concrete with Portland cement binder at equivalent w/b ratio. First Published Online: 26 Jul 2012